KUALITAS PUPUK KOMPOS DENGAN BAHAN DASAR FESES DAN SISA PAKAN TERNAK SAPI - Andri Dwi Yulianto; Catur Suci Purwati (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2026)
This study aims to evaluate the effectiveness of utilizing cow dung and animal feed waste as raw materials for composting on the quality of macronutrient content including nitrogen (N), phosphorus (P), and potassium (K). The background of this study is based on the importance of managing livestock waste into useful products for the agricultural sector as well as an environmentally friendly solution to improve soil structure and support sustainable agricultural systems. The research method was carried out by applying five treatment levels, namely P0 as a control, and P1, P2, P3, and P4 which involved the addition of EM4 activator up to a concentration of 5%. The results of the analysis showed that in the nitrogen parameter, the highest average was achieved by treatment P3 at 0.59, followed by P4 (0.57) and P0 (0.55), but statistically the results showed no significant difference (P <0.05) across all treatments. This indicates that treatment variations have not been able to significantly increase nitrogen content, which is thought to be due to the uniform decomposition process and the risk of nitrogen loss in the form of ammonia during the composting process. In contrast, for the phosphorus parameter, the P4 treatment produced the highest yield of 0.39 and showed a significant difference compared to the other treatments, with the lowest value at P0 of 0.28. The effectiveness of P4 in increasing phosphorus is closely related to the optimal activity of phosphate-solubilizing microorganisms in breaking down organic compounds into inorganic compounds that are available to plants. The most significant increase was seen in the potassium parameter, where the P4 treatment produced the highest value of 0.85, followed by P3 (0.71), P2 (0.67), P1 (0.61), and P0 (0.43). Statistical analysis showed that the treatment had a very significant effect on potassium levels, which was influenced by the high original mineral content in the raw materials and the effectiveness of the decomposition process in breaking down complex minerals into readily absorbable elements. Overall, the study concluded that the application of EM4 up to 5% had a very significant effect on increasing potassium, but did not have a statistically significant effect on nitrogen and phosphorus content in the final conclusion. The use of this technology has proven effective in reducing livestock waste and optimizing the overall quality of organic fertilizer.